Epidemiological Transition in Rural Bangladesh, 1986-2006 - Ahsan Karar, Z. (2012)
BACKGROUND: For understanding epidemiological transition, Health and Demographic Surveillance System plays an important role in developing and resource-constraint setup where accurate information on vital events (e.g. births, deaths) and cause of death is not available. METHODS: This study aimed to assess existing level and trend of causes of 18,917 deaths in Matlab, a rural area of Bangladesh, during 1986-2006 and to project future scenarios for selected major causes of death. RESULTS: The results demonstrated that Matlab experienced a massive change in the mortality profile from acute, infectious, and parasitic diseases to non-communicable, degenerative, and chronic diseases during the last 20 years. It also showed that over the period 1986-2006, age-standardized mortality rate (for both sexes) due to diarrhea and dysentery reduced by 86%, respiratory infections by 79%, except for tuberculosis which increased by 173%. On the other hand, during the same period, mortality due to cardiovascular and cerebrovascular diseases increased by a massive 3,527% and malignant neoplasms by 495%, whereas mortality due to chronic obstructive pulmonary disease and injury remained in the similar level (12-13% increase). CONCLUSION: The trend of selected causes of death demonstrates that in next two decades, deaths due to communicable diseases will decline substantially and the mortality due to non-communicable diseases (NCDs) will increase at massive proportions. Despite Matlab's significant advances in socio-demographic indicators, emergence of NCDs and mortality associated with it would be the major cause for concern in the coming years.